Selected base sequence outside the target binding site of zinc finger protein Sp1 - Nagaoka, Makoto (Oxford University Press, 2001)
Human transcription factor Sp1 contains three contiguous repeats of the C(2)H(2)-type zinc finger motif and binds to the decanucleotide sequence 5′-(G/T)GGGCGG(G/A)(G/A)(C/T)-3′ (GC box). In order to determine whether the three-zinc finger peptide Sp1(530–623) has selectivity for sequence outside the GC box, we used a selection and amplification of binding experiment. The high affinity sequence generated from this selection is 5′-GGGTGGGCGTGGC-3′ (s-GC box), which is flanked by a novel conserved guanine triplet on the 5′-side of the core decanucleotide. Gel mobility shift assays reveal that Sp1(530–623) binds to the s-GC box with 2.3-fold higher affinity than to the wild-type GC box, 5′-GGGGCGGGGC-3′ (c-GC box). DNase I and hydroxyl radical footprinting analyses show that the area of the s-GC box protected by binding of Sp1(530–623) is wider by 1 nt than that of the c-GC box. On the other hand, alkylation interference analyses demonstrate that Sp1(530–623) forms only one special base contact at the guanine triplet. With respect to cleavage of the c-GC and s-GC boxes by the 1,10-phenanthroline–copper complex (OP-Cu), binding of Sp1(530–623) has no effect on the cleavage pattern of the s-GC box, whereas OP-Cu actually enhances cleavage of the c-GC box. Additionally, the extent of cleavage of the s-GC box by DNase I and OP-Cu is clearly different from that of the c-GC box under peptide-free conditions. The results strongly indicate that: (i) the conformation of the s-GC box is evidently distinct from that of the c-GC box; (ii) Sp1(530–623) binds to the s-GC box without induction of a conformational change in DNA detectable by cleavage with OP-Cu. The present study provides useful information for the design of multi-zinc finger proteins with various sequence specificities.